“Alterations in the Skin Microbiota Are Associated With Symptom Severity in Mycosis Fungoides” - Zhang, Yumeng; Seminario-Vidal, Lucia; Cohen, Leah; Hussaini, Mohammad; Yao, Jiqiang; Rutenberg, David; Kim, Youngchul; Giualiano, Anna; Robinson, Lary A.; Sokol, Lubomir (Frontiers in Cellular and Infection Microbiology, 2022)
Cutaneous T cell lymphoma (CTCL), a non-Hodgkin lymphoma, is thought to arise from mature tissue-resident memory T cells. Mycosis fungoides (MF) is the most common subtype. The role of skin microbiota in the symptom manifestation of MF remains unclear. Among 39 patients with MF, we analyzed bacteria colonizing MF lesions and non-lesional skin in the contralateral side and characterized regional changes in the skin microbiota related to MF involvement using the difference in relative abundance of each genus between lesional and contralateral non-lesional skin. We investigated the relationship between these skin microbiota alterations and symptom severity. There was no statistically significant difference in bacterial diversity and richness between lesional and non-lesional skin. Different skin microbiota signatures were associated with different symptoms. An increase in Staphylococcus in lesional skin was associated with pronounced erythema, and a decrease in Propionibacterium in lesional skin was associated with increased pain and skin thickness. The results of this pilot study suggest that the skin microbiota plays an important role in changing disease phenotypes among patients with MF. Larger skin microbiota studies of patients with MF may further characterize these differences and support the use of antibiotic treatment to mitigate CTCL symptoms.